2007
DOI: 10.1128/jvi.02453-06
|View full text |Cite
|
Sign up to set email alerts
|

A Replication-Competent Adenovirus-Human Immunodeficiency Virus (Ad-HIV)tatand Ad-HIVenvPriming/Tat and Envelope Protein Boosting Regimen Elicits Enhanced Protective Efficacy against Simian/Human Immunodeficiency Virus SHIV89.6PChallenge in Rhesus Macaques

Abstract: We previously demonstrated that replication-competent adenovirus (Ad)-simian immunodeficiency virus (SIV) recombinant prime/protein boost regimens elicit potent immunogenicity and strong, durable protection of rhesus macaques against SIV mac251 . Additionally, native Tat vaccines have conferred strong protection against simian/human immunodeficiency virus SHIV 89.6P challenge of cynomolgus monkeys, while native, inactivated, or vectored Tat vaccines have failed to elicit similar protective efficacy in rhesus m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
81
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(87 citation statements)
references
References 59 publications
4
81
2
Order By: Relevance
“…When corrected for multiple comparisons in a multi-arm vaccine study, this protection was no longer statistically significant [44]. In the cynomolgus model, however, MHC class IB haplotypes were seen to influence the course of SHIV 89.6P infection.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…When corrected for multiple comparisons in a multi-arm vaccine study, this protection was no longer statistically significant [44]. In the cynomolgus model, however, MHC class IB haplotypes were seen to influence the course of SHIV 89.6P infection.…”
Section: Discussionmentioning
confidence: 93%
“…Immunizations with Tat plus Rev and Tat plus other nonstructural HIV gene products have shown protection against SIV [45,46]. A potential synergy between Tat and Env leading to enhanced protective efficacy in rhesus macaques against SHIV 89.6P was recently reported [44]. Prospective studies using Tat-based vaccine strategies are being conducted in non-human primates typed to control for host susceptibility/resistance factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, vaccine-induced T-cell and humoral immune responses were not sufficient to protect animals from SHIV 89.6p infection, but immunized animals that became infected were protected from disease progression for more than a year (66 weeks), while the majority of control animals developed evidence of AIDS-like disease. Others also have previously shown vaccine-induced control of the SHIV 89.6P load and protection from disease progression (3,8,19,21,24). It is possible that protection is relatively easy to induce in the challenge model used (25).…”
Section: Discussionmentioning
confidence: 99%
“…Also, a replication-defective adenovirus (Ad)-type 5 (Ad5)-HIV tat vaccine (86 aa) failed to protect rhesus macaques against homologous SHIV 89.6P challenge administered intravenously [180]. Finally, other studies in rhesus macaques showed that priming with a replication-competent Ad5-HIV tat vector and boosting with the Tat protein (86 aa) did not protect against intravenous challenge with homologous SHIV 89.6P [181]. Although the reasons for these conflicting results are not known, it is likely that the different outcomes of infection may reflect species differences with regard to immunogenicity or host resistance factors; difference in vaccine characteristics; immunization protocol; timing and route of administration; delivery systems; and/or type, dose, and route of administration of the challenge virus.…”
Section: Preclinical Studies With Hiv-1 Tat Vaccinesmentioning
confidence: 99%